2018
DOI: 10.1016/j.bpj.2018.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Dystrophin’s Actin-Binding Domain

Abstract: We have used pulsed electron paramagnetic resonance, calorimetry, and molecular dynamics simulations to examine the structural mechanism of binding for dystrophin's N-terminal actin-binding domain (ABD1) and compare it to utrophin's ABD1. Like other members of the spectrin superfamily, dystrophin's ABD1 consists of two calponin-homology (CH) domains, CH1 and CH2. Several mutations within dystrophin's ABD1 are associated with the development of severe degenerative muscle disorders Duchenne and Becker muscular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
2
6
0
Order By: Relevance
“…We extend this model by showing not only that the 'open' utrophin CH1-CH2 can be made 'more open' and higher affinity but also that an unstructured linker can reduce CH2 steric clash and increase CH1-CH2 affinity, offering a mechanism for titrating 'openness' to vary affinity. This notion is consistent with MD simulations and DEER measurements that have shown that the CH domains from dystrophin can adopt a range of conformations (Fealey et al, 2018). We show that these mechanisms of affinity modulation can be additively combined with others, such as N-terminal region modifications, to create domains with diverse affinities and levels of openness.…”
Section: Discussionsupporting
confidence: 89%
“…We extend this model by showing not only that the 'open' utrophin CH1-CH2 can be made 'more open' and higher affinity but also that an unstructured linker can reduce CH2 steric clash and increase CH1-CH2 affinity, offering a mechanism for titrating 'openness' to vary affinity. This notion is consistent with MD simulations and DEER measurements that have shown that the CH domains from dystrophin can adopt a range of conformations (Fealey et al, 2018). We show that these mechanisms of affinity modulation can be additively combined with others, such as N-terminal region modifications, to create domains with diverse affinities and levels of openness.…”
Section: Discussionsupporting
confidence: 89%
“…We speculate that the large difference in off-rate implies that reduced inter-CH domain interactions allow the domain to adopt a high-affinity state when bound to F-actin, potentially through reduced steric interactions between CH2 and F-actin. This notion is consistent with measurements that have shown that the CH domains from dystrophin and utrophin can adopt a range of conformations in solution, only some of which are potentially compatible with F-actin binding (Fealey et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…The full-length dystrophin isoform Dp427-M belongs to the class of giant muscle proteins [ 50 ] and consists of several distinct molecular domains as illustrated in the upper panel of Figure 1 . This includes amino-terminal and central actin-binding domains, proline-rich hinge regions, spectrin-like rod domains and crucial carboxy-terminal binding sites for interactions with plasmalemmal and cytosolic components [ 51 , 52 , 53 , 54 ]. Dystrophin closely interacts with the integral proteins beta-dystroglycan, alpha/beta/gamma/delta-sarcoglyan and sarcospan of the sarcolemma, the extracellular receptor alpha-dystroglycan and laminin-211, the cytosolic components alpha/beta-dystrobrevin and alpha/beta-syntrophin, and the cortical actin cytoskeleton [ 9 , 10 , 11 , 12 , 13 ], as shown in the lower panel of Figure 1 .…”
Section: The Core Dystrophin Complex In Skeletal Musclementioning
confidence: 99%